Two novel loci, COBL and SLC10A2, for Alzheimer's disease in African Americans. Issue 2 (19th October 2016) - Mez, Jesse; Chung, Jaeyoon; Jun, Gyungah; Kriegel, Joshua; Bourlas, Alexandra P.; Sherva, Richard; Logue, Mark W.; Barnes, Lisa L.; Bennett, David A.; Buxbaum, Joseph D.; Byrd, Goldie S.; Crane, Paul K.; et al.
Abstract: Introduction: African Americans' (AAs) late‐onset Alzheimer's disease (LOAD) genetic risk profile is incompletely understood. Including clinical covariates in genetic analyses using informed conditioning might improve study power. Methods: We conducted a genome‐wide association study (GWAS) in AAs employing informed conditioning in 1825 LOAD cases and 3784 cognitively normal controls. We derived a posterior liability conditioned on age, sex, diabetes status, current smoking status, educational attainment, and affection status, with parameters informed by external prevalence information. We assessed association between the posterior liability and a genome‐wide set of single‐nucleotide polymorphisms (SNPs), controlling for APOE and ABCA7, identified previously in a LOAD GWAS of AAs. Results: Two SNPs at novel loci, rs112404845 ( P  = 3.8 × 10 −8 ), upstream of COBL, and rs16961023 ( P  = 4.6 × 10 −8 ), downstream of SLC10A2, obtained genome‐wide significant evidence of association with the posterior liability. Discussion: An informed conditioning approach can detect LOAD genetic associations in AAs not identified by traditional GWAS.